Responsibilities and Competencies for Health Education Specialists: Implications for Research and Practice in the American Journal of Health Education. Issue 1 (2nd January 2021) - Eifert, Elise; Chaney, Beth; Redican, Kerry; Eddy, Jim
ABSTRACT: The American Journal of Health Education (AJHE) has been published for over 50 years. Over time, the mission and goal of AJHE have evolved from a publication focused primarily on school health issues in the United States to an international journal focused on chronic disease, and related lifestyle factors, for health education and health promotion researchers and practitioners, Certified Health Education Specialists (CHES®) and Master Certified Health Education Specialist (MCHES®).  The purpose of this feature article is to discuss how the Responsibilities and Competencies for Health Education Specialists articulate with the mission of the American Journal of Health Education .